National Team Fans: Is Passion Enough to Leverage Sponsor Brands? - Leal, C.; Dionísio, J.; Brochado, A. (Multidisciplinary Perspectives on Media Fandom, 2020)
Football (i.e., soccer) is the most popular sport in Portugal, whose national team is considered a symbol of the entire country. This study sought to identify this team's fan profile and brand image's main components and the main determinants of the team's sponsorship effectiveness. Data were collected on fans several weeks before the 15th Union of European Football Associations Euro 2016. This study's initial qualitative phase was followed by a quantitative phase. Thirty face-to-face interviews were conducted, after which 801 fans filled out a survey. Qualitative analysis identified nine image associations that Portuguese fans link with their national team: national symbol, pride, passion, strength, strong emotions, happiness, optimism, connection, and positive feelings. Four clusters of fans' expectations and demographics were found, confirming heterogeneity. The team's sponsorship effectiveness is stronger for sponsors' clients and highly involved fans, as well as when brand image congruence exists between sponsors and the sponsee.